Digital Transformation in Guidance and Counseling: The Influence of Website Media on Students’ Self-Awareness - Annisa, Dona Fitri; Utomo, Prio; Costa, Augusto da (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2025)
Digital transformation in guidance and counseling leverages website media to enhance students’ self-awareness, adapting to technological advancements in education. This study aims to test the effectiveness of website media in increasing students’ self-awareness through group guidance services. The research method uses the Research and Development (R&D) approach with the continuous Borg & Gall model, involving class X students of SMK Mahardhika Batujajar. The research instrument is a self-awareness scale, with data analysis through the Kolmogorov-Smirnov and Shapiro-Wilk normality tests and the paired sample t-test effectiveness test. The results showed a significant increase in students’ self-awareness, with a total pretest score of 1,224 increasing to 1,745 in the posttest. The normality test showed that the data was normally distributed with a Kolmogorov-Smirnov significance value of 0.261 and Shapiro-Wilk 0.726 (> 0.05). The paired sample t-test effectiveness test showed a Sig. (2-tailed) value of 0.000, which means that there is a significant difference between the pretest and posttest. In conclusion, website-based media has proven effective in increasing students’ self-awareness with a more flexible and interactive approach. The contribution of this research includes a strategy for developing more adaptive technology-based guidance, providing more effective alternatives for students, and being a reference for teachers and counselors in integrating digital media in guidance and counseling services.